Efficient Li‐Ion‐Conductive Layer for the Realization of Highly Stable High‐Voltage and High‐Capacity Lithium Metal Batteries. Issue 13 (14th February 2019) - Lee, Jung‐In; Shin, Myungsoo; Hong, Dongki; Park, Soojin
Abstract: Recently, a consensus has been reached that using lithium metal as an anode in rechargeable Li‐ion batteries is the best way to obtain the high energy density necessary to power electronic devices. Challenges remain, however, with respect to controlling dendritic Li growth on these electrodes, enhancing compatibility with carbonate‐based electrolytes, and forming a stable solid–electrolyte interface layer. Herein, a groundbreaking solution to these challenges consisting in the preparation of a Li2 TiO3 (LT) layer that can be used to cover Li electrodes via a simple and scalable fabrication method, is suggested. Not only does this LT layer impede direct contact between electrode and electrolyte, thus avoiding side reactions, but it assists and expedites Li‐ion flux in batteries, thus suppressing Li dendrite growth. Other effects of the LT layer on electrochemical performance are investigated by scanning electron microscopy, electrochemical impedance spectroscopy, and galvanostatic intermittent titration technique analyses. Notably, LT layer‐incorporating Li cells comprising high‐capacity/voltage cathodes with reasonably high mass loading (LiNi0.8 Co0.1 Mn0.1 O2, LiNi0.5 Mn1.5 O4, and LiMn2 O4 ) show highly stable cycling performance in a carbonate‐based electrolyte. Therefore, it is believed that the approach based on the LT layer can boost the realization of high energy density lithium metal batteries and next‐generation batteries. Abstract : The ex situ‐formed artificial layer of Li2 TiO3, which is characterized by having a 3D pathway that enables Li ions to migrate through it, is developed to improve Li‐ion flux uniformly and suppress indiscriminate Li dendrites in Li metal batteries. The synergetic effects of the layer realize high‐energy full cells combined with high‐capacity and high‐voltage cathodes.